Effectiveness and safety of methotrexate monotherapy in patients with Crohn's disease refractory to anti‐TNF‐α: results from the ENEIDA registry. Issue 9 (14th March 2021) - Mesonero, Francisco; Castro‐Poceiro, Jesús; Benítez, Jose M.; Camps, Blau; Iborra, Marisa; López‐García, Alicia; Torres, Paola; Esteve, María; Tosca, Joan; Bertoletti, Federico; Almela, Pedro; Calvet, Xavier; et al.
Summary: Background: Methotrexate can be used to maintain remission in Crohn's disease patients who are intolerant to thiopurines. Data on its use as monotherapy in other scenarios are limited. Aim: To assess the effectiveness of methotrexate monotherapy in Crohn's disease patients after previous failure to anti‐tumour necrosis factor (anti‐TNFα) drugs. Methods: A retrospective, observational multicentre study of data from the Spanish ENEIDA registry. Participants were patients with active Crohn's disease and previous failure to anti‐TNFα started on methotrexate monotherapy. Short‐term effectiveness was assessed at 12‐16 weeks based on Harvey‐Bradshaw index (HBI): clinical remission as HBI ≤ 3 points and clinical response as HBI drop of ≥ 3 points over baseline. Long‐term effectiveness was defined as steroid‐free methotrexate persistence from 12 to 16 weeks until maximum follow up. Adverse events were recorded. Results: Data were compiled for 110 patients treated with methotrexate after a failed response to one (39%) or two (55.6%) anti‐TNFα agents. Short‐term clinical response and remission rates were 60% and 30.9% respectively. Of 74 patients who continued after week 16, long‐term effectiveness was achieved in 82% and 74% at 12 and 24 months respectively. In the multivariate analysis, non‐remission at short term (vs remission) was associated with long‐term failure (HR 2.58, 95%CI 1.95‐3.68, P  = 0.028). Adverse events (evaluated in 100 patients) were recorded in 44%, and in 30.4% of these patients, they led to methotrexate discontinuation. Conclusions: The benefits observed suggest methotrexate monotherapy could be a valid option in Crohn's disease patients with previous failure to anti‐TNFα. Abstract :